ANALYSIS OF EFFICIENCY OF THE DISTANCE TRAINING SYSTEM IN THE PROCESS OF COMPETENCY VERIFICATION - Kravtsovа Л.В.; Zaytseva Т.В.; Kaminskaya Н.Г. (Journal of Information Technologies in Education (ITE), 2017)
The Kherson State Maritime Academy conducts experimental research on the integration of the educational process on the basis of a competence approach to the state educational policy of Ukraine. One of the directions of this work is the creation and implementation of a distance education platform to support the educational process in the Kherson Maritime Academy. The distance learning system of KSMA is built on the basis of the open Moodle platform,which offers a wide range of opportunities to fully support the learning process in the remote environment, namely, a variety of ways of presenting the training material, testing knowledge and monitoring progress.The peculiarity of the developed system is that the effectiveness of the training strategy is provided by taking into account the psychological characteristics of the user contingent,the ultimate goal of training, the motivation of the whole process of education, namely, the specifics of the seaman’s profession. One of the main directions of the work was a complete replacement of the classical methodology for conducting the examination session for complex testing, which covers all disciplines from 1 to 5 courses of study and is conducted on the basis of a distance education platform. The results of the experiment showed that own site of distance learning is an effective tool for studying the teaching material and for testing the quality of its learning.